Physiological and physico-chemical changes in 'sinta' papaya (Carica papaya L.) during storage at different temperatures - Mercadero, R. D.; Esguerra, E. B. (2000)
The physiological and physico-chemical changes in 'Sinta' papaya fruits were characterized during storage at 12, 15, ambient (28-30 C), 20 and 25 C to determine the optimum temperature for storage and ripening.

Respiration and ethylene production peaked on the 6th and 8th day at ambient temperature and 20-25 C, respectively. At 12 and 15 C, these peaks occurred on day 19 and 20, respectively. At all these temperatures, CO2 and ethylene production peaks ranged from 59-75 mg kg⁻¹ h⁻¹ and 0.36-0.48 mL kg⁻¹ h⁻¹, respectively, when peel color was more yellow than green. Fruits stored at higher temperatures (20, 25 C and ambient) ripened fast, attaining full yellow peel color on the 11th, 10th and 8th day, respectively. At 12 and 15 C, fruits remained at color break until the 7th day, more green than yellow on the 14th day, and full yellow with tinge of green on the 21st day of storage. Symptoms of chilling injury and high disease incidence were observed in fruits stored for 2 or 3 weeks at 12 and 15 C, respectively, before transfer to 25 C. Prolonged storage at low temperatures decreased fruit firmness. At ripening, there were no significant differences in the total soluble solids content and pH of fruits stored at different temperatures. A significantly higher titratable acidity value was obtained in fruits stored for 1 week at 15 C than those held at 25 and 12 C. Regardless of storage temperature, sensory scores of taste panelists did not differ significantly except for sweetness. Fruits kept at 12 C received a low rating.

The optimum temperature for ripening 'Sinta' papaya is 20-25 C with the fruits attaining uniform ripening and good peel coloration. For prolonged storage, fruits can be kept at 15 C for 2 weeks and then transferred at 25 C for ripening. At 12 C, normal ripening upon transfer to 25 C can be obtained only when fruits are held for 1 week.
Keywords: Papaya; Fruit storage; Physiological adaptation; Chemical reactions